Análisis del comercio electrónico en las MIPYMES del cantón El Carmen de la provincia de Manabí - Lago Zambrano, Alisson Nicolle (2023)
The present investigation was developed in El Carmen canton, Manabí province, an interview was carried out with the entrepreneurs of the MSMEs to know the strengths and limitations of electronic commerce, allowing to obtain a general projection for the achievement of the first objective, as well as a design of schemes was carried out based on the information obtained, in relation to the types of research, bibliographic and field research was used and the application of inductive, deductive, analytical and historical methods. After this, a survey was carried out to know the decision elements that influence consumers when carrying out electronic commerce transactions in El Carmen canton. Compiling the results, it was determined that one of the factors that limit or contribute to electronic commerce in MSMEs is the lack of knowledge and time on the part of administrators and consumers' fear of being scammed or that the product does not meet their expectations. Finally, an improvement plan was proposed aimed at the results of the factors that were limiting electronic commerce in MSMEs in El Carmen canton in Manabí province.